ВЛИЯНИЕ КОЛЛЕКТОРНО-ДРЕНАЖНЫХ ВОД НА СВОЙСТВА ПОЧВ ПУСТЫННОЙ ЗОНЫ (Scientific journal of the Fergana State University, 2023)
As a result of long-term research influence of the low-mineralized collector and drainage exhaust waters on properties irrigated sasa meadow soils of heavy loamy mechanical structure is established their negative influence on structure and amounts of water-soluble salts of soils and ground waters, on structure of the absorbed bases, ionic force, on quantity and quality of a humus and other properties of soils.